Downwind: A People's History of the Nuclear West - Fox, Sarah Alisabeth (UNP - Bison Books, 2014)
Downwindis an unflinching tale of the atomic West that reveals the intentional disregard for human and animal life through nuclear testing by the federal government and uranium extraction by mining corporations during and after the Cold War. Sarah Alisabeth Fox highlights the personal cost of nuclear testing and uranium extraction in the American West through extensive interviews with "downwinders," the Native American and non-Native residents of the Great Basin region affected by nuclear environmental contamination and nuclear-testing fallout. These downwinders tell tales of communities ravaged by cancer epidemics, farmers and ranchers economically ruined by massive crop and animal deaths, and Native miners working in dangerous conditions without proper safety equipment so that the government could surreptitiously study the effects of radiation on humans. In chilling detailDownwindbrings to light the stories and concerns of these groups whose voices have been silenced and marginalized for decades in the name of "patriotism" and "national security." With the renewed boom in mining in the American West, Fox's look at this hidden history, unearthed from years of field interviews, archival research, and epidemiological studies, is a must-read for every American concerned about the fate of our western lands and communities.